2004
DOI: 10.1016/j.jacc.2003.08.040
|View full text |Cite
|
Sign up to set email alerts
|

Effects of glycoprotein iib/iiia inhibition on microvascular flow after coronary reperfusion

Abstract: As demonstrated by QMCE, GPI improves microvascular flow and reduces the infarct area after coronary occlusion/reperfusion, independent of epicardial flow. These data demonstrate the usefulness of QMCE in assessing microvascular flow, provide novel evidence for the role of platelets in the early phase of reperfusion injury, and show that GPI is of value in preserving microvascular perfusion after coronary reperfusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
59
0
2

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(67 citation statements)
references
References 38 publications
6
59
0
2
Order By: Relevance
“…Using quantitative myocardial contrast echocardiographic study, tirofiban also improved microvascular flow and reduced the infarct area after coronary occlusion/reperfusion in open-chest dogs. 12) This ex vivo observation was also evident clinically. For example, intracoronary administration of abciximab, 13) a monoclonal antibody directed against the glycoprotein IIb/IIIa receptor, and tirofiban, 14) a synthetic nonpeptide small-molecule platelet glycoprotein IIb/ IIIa receptor inhibitor, were shown to be able to dissolve an intracoronary thrombus, although both are not thrombolytic agents.…”
Section: Discussionmentioning
confidence: 67%
“…Using quantitative myocardial contrast echocardiographic study, tirofiban also improved microvascular flow and reduced the infarct area after coronary occlusion/reperfusion in open-chest dogs. 12) This ex vivo observation was also evident clinically. For example, intracoronary administration of abciximab, 13) a monoclonal antibody directed against the glycoprotein IIb/IIIa receptor, and tirofiban, 14) a synthetic nonpeptide small-molecule platelet glycoprotein IIb/ IIIa receptor inhibitor, were shown to be able to dissolve an intracoronary thrombus, although both are not thrombolytic agents.…”
Section: Discussionmentioning
confidence: 67%
“…In a study carried out by Assali et al (39), 5.9% of the patients administered with intracoronary adenosine were observed with no-reflow, while the ratio of patients with noreflow was 28.6% in the group not receiving adenosine. Kunichika et al (40) reported that tirofiban, a glycoprotein receptor inhibitor, decreased the extent of infarct and no-reflow incidence. Lower incidence of no-reflow phenomenon has been reported in patients undergoing direct stenting without predilation (41).…”
Section: Discussionmentioning
confidence: 99%
“…This no-reflow phenomenon is thought to be the result of microvascular obstruction (17)(18)(19). This phenomenon is a marker of more extensive myocardial tissue damage and has been proven to be associated with poorer functional recovery, an increased frequency of heart failure and poor survival (4,20). This is why there is a growing need to establish a reliable marker of myocardial perfusion.…”
Section: Discussionmentioning
confidence: 99%